Dimensions of equity and social justice in Latin America and Brazil - Elisa P. Reis; André P. Vieira; Felix G. Lopez (economic sociology. perspectives and conversations, 2023)
In a world that claims to value equality, inequality persists and in many ways is even growing, despite the ethical and pragmatic challenges it poses to social, political, and economic life dimensions. Yet, progressive movements, driven by ideals and interests, emphasize the importance of equity and justice.
Keywords: 300